Characterization and Antioxidant Activity of Fermented Milk Produced with a Starter Combination - Marya, Dina Tri; Nurliyani; Widodo; Sunarti (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to evaluate the microbiological and chemical characteristics and antioxidant activity of fermented milk produced by different starter combinations. Materials and Methods: Nine combinations of starter produced fermented dairy products using single-starter Lactic Acid Bacteria (LAB), a combination of starter LAB and a combination of starter LAB and yeast. The starter combinations were as follows: Lactobacillus plantarum Dad 13, L. plantarum Dad 13+Lactococcus lactis, L. plantarum Dad 13+Saccharomyces cerevisiae, L. plantarum Dad 13+Kluyveromyces marxianus, L. plantarum Dad 13+L. lactis+S. cerevisiae, L. plantarum Dad 13+L. lactis+K. marxianus, L. lactis, L. lactis+S. cerevisiae and L. lactis+K. marxianus. Total LAB and yeast were analyzed using the Total Plate Count (TPC) method. Chemical characteristics were identified by the values of pH, titratable acidity and ethanol contents. Antioxidant activities were determined by calculating the percentage of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Results: Present study showed that the combination of starters did not differ significantly across total LAB and yeast. However, there were significantly differences in pH, acidity, alcohol, β-carotene and antioxidant activity. The fermented milk obtained from L. plantarum Dad 13+L. lactis+K. marxianus had the lowest pH and the highest acidity and alcohol content. The combination L. plantarum Dad 13+L. lactis+S. cerevisiae produced the maximum β-carotene content and the combination of L. plantarum Dad 13+ L. lactis+S. cerevisiae had the best antioxidant activity. Conclusion: It is concluded that a combination of starter L. plantarum Dad 13, L. lactis and S. cerevisiae can be used to improve the chemical quality and antioxidant activity of fermented milk.